PEMBENTUKAN LOYALITAS PELANGGAN MELALUI CITRA MEREK DAN KUALITAS PRODUK - Tun Ganyang, Machmed (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to examine the relationship between brand image and product quality on customer loyalty in sports products. Data were collected through a questionnaire of 68 respondents. Through regression analysis, the results show that brand image and quality can explain variations in consumer loyalty with the brand image as a dominant factor. This finding implies that producers can increase consumer loyalty by enhancing brand image. Companies need to think about how to develop key messages so that consumers can clearly understand the position of the product. The unique aspects of the product need to be improved to create a special impression on the customer.